Pollen morphology of eight tribes of Asteraceae from Universitas Indonesia Campus, Depok, Indonesia - ANDI SALAMAH; RACHMI LUTHFIKASARI; ASTARI DWIRANTI (Society for Indonesian Biodiversity, 2019)
Salamah A, Luthfikasari R, Dwiranti A. 2019. Pollen morphology of eight tribes of Asteraceae from Universitas Indonesia Campus, Depok, Indonesia. Biodiversitas 20: 152-159. Asteraceae is one of the largest flowering plant families in the world consisting of a high diversity of species that possess many macro-morphological characters. Ecological pressures have resulted in this highly varied morphology. Our research aims to describe the pollen morphology of the Asteraceae for species occurring in Depok Campus of Universitas Indonesia. Pollens of 14 species from eight tribes were extracted using acetolysis method and observed under a light microscope. The result showed that pollen unity, shape and pollen surface appeared to be differentiating characters of the Asteraceae from other families, while polarity and symmetry characters can be distinguishing characters at higher levels of the family such as subdivisions. Aperture characters were useful to differentiate between tribes. The shape of pores and size of pollen were not useful in differentiating between tribes, but may differentiate between lower taxa. The results of this study could be used as supporting data for regrouping taxa within the Asteraceae using morphological features.